2019
DOI: 10.3390/ijerph16101841
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Locus of Control, Agents of Socialization and Sport Socialization Situations on the Sports Participation of Women in Taiwan

Abstract: Compared to men, the sports participation of women is lower, especially in the East. Not many studies have compared the impacts of locus of control, agents of socialization, and sport socialization situations on the sports participation of women. Hence, the purpose of this study is to explore the contributing factors which may promote the sports participation of women in Taiwan. To do this, 450 structured questionnaires were distributed to women in Chiayi, Taiwan, with an 89.3% return rate. The study found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Further, according to Towers et al [ 41 ], developing an IHLC promotes exercise and sports participation by decreasing resistance toward exercise. Similarly, Huang et al [ 42 ] suggested that having an IHLC promotes women’s sports participation. However, in that study, IHLC was statistically strengthened only when participants participated in sports at least four times per week, at least 60 min per session, over a period of six months or more; therefore, it can be interpreted that sporadic sports participation had a very slight or little effect on IHLC.…”
Section: Discussionmentioning
confidence: 99%
“…Further, according to Towers et al [ 41 ], developing an IHLC promotes exercise and sports participation by decreasing resistance toward exercise. Similarly, Huang et al [ 42 ] suggested that having an IHLC promotes women’s sports participation. However, in that study, IHLC was statistically strengthened only when participants participated in sports at least four times per week, at least 60 min per session, over a period of six months or more; therefore, it can be interpreted that sporadic sports participation had a very slight or little effect on IHLC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such incidents will further limit female participation in sports in the country. These views are supported by Huang, Liu, Chang, Hsieh, Lu (2019), which stated that when community sports facilities are provided, it can encourage the public to participate in sports activities. Chien (2013) further asserts this theory and also argued that the right sports environment promotes active participation.…”
Section: Inadequate Sports Facilities and Equipmentmentioning
confidence: 99%
“…The few sports equipment and facilities are grossly mismanaged and present to men first before they are available to women (Saavedra & Martha, 2010). Huang et al (2019) stated that providing community sports facilities have impacts that are more significant on public participation in sports. Chien (2013), who argued that the sports environment could enhance motivation to engage in sporting activities, primarily when factors such as aesthetics, support, safety, extensity and accessibility are all accounted for, equally asserted these.…”
Section: Unavailability Of Sports Facilities and Equipmentmentioning
confidence: 99%